Inhaled 45–50% argon augments hypothermic brain protection in a piglet model of perinatal asphyxia - Kevin D. Broad; Igor Fierens; Bobbi Fleiss; Eridan Rocha-Ferreira; Mojgan Ezzati; Jane Hassell; Daniel Alonso-Alconada; Alan Bainbridge; Go Kawano; Daqing Ma; Ilias Tachtsidis; Pierre Gressens; et al. (Neurobiology of Disease, 2016)
Cooling to 33.5 °C in babies with neonatal encephalopathy significantly reduces death and disability, however additional therapies are needed to maximize brain protection. Following hypoxia–ischemia we assessed whether inhaled 45–50% Argon from 2–26 h augmented hypothermia neuroprotection in a neonatal piglet model, using MRS and aEEG, which predict outcome in babies with neonatal encephalopathy, and immunohistochemistry. Following cerebral hypoxia–ischemia, 20 Newborn male Large White piglets < 40 h were randomized to: (i) Cooling (33 °C) from 2–26 h (n = 10); or (ii) Cooling and inhaled 45–50% Argon (Cooling + Argon) from 2–26 h (n = 8). Whole-brain phosphorus-31 and regional proton MRS were acquired at baseline, 24 and 48 h after hypoxia–ischemia. EEG was monitored. At 48 h after hypoxia–ischemia, cell death (TUNEL) was evaluated over 7 brain regions. There were no differences in body weight, duration of hypoxia–ischemia or insult severity; throughout the study there were no differences in heart rate, arterial blood pressure, blood biochemistry and inotrope support. Two piglets in the Cooling + Argon group were excluded. Comparing Cooling + Argon with Cooling there was preservation of whole-brain MRS ATP and PCr/Pi at 48 h after hypoxia–ischemia (p < 0.001 for both) and lower 1H MRS lactate/N acetyl aspartate in white (p = 0.03 and 0.04) but not gray matter at 24 and 48 h. EEG background recovery was faster (p < 0.01) with Cooling + Argon. An overall difference between average cell-death of Cooling versus Cooling + Argon was observed (p < 0.01); estimated cells per mm2 were 23.9 points lower (95% C.I. 7.3–40.5) for the Cooling + Argon versus Cooling. Inhaled 45–50% Argon from 2–26 h augmented hypothermic protection at 48 h after hypoxia–ischemia shown by improved brain energy metabolism on MRS, faster EEG recovery and reduced cell death on TUNEL. Argon may provide a cheap and practical therapy to augment cooling for neonatal encephalopathy.